2020
DOI: 10.13031/trans.12612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shake-and-Catch Methods on Harvesting of Tall Spindle Apples

Abstract: HighlightsBoth frequency and amplitude were influencing factors in analyzing the fruit removal efficiency and fruit damage.This research focused on tall spindle ‘Fuji’ apple trees, which enriched the study of the variety and architecture resources of apple trees.The advice for shake-and-catch harvesting was based on the analysis of amplitude and frequency from the perspective of energy consumption.Abstract. Almost all fresh-market apples are picked manually, and these apples rank among the most labor-intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Obviously, almost all of the mechanical shaking systems are employed to harvest fruits for processing industry on account of the fruit damage. While a few researchers investigated that the limb shaking system could also be used for the fresh apple harvesting effectively [23][24][25]29,126] . It indicated that limb shaker with catching device would be a promising pattern to harvest fruits selectively with relative high fruit removal percentage and low fruit injury for fresh fruit market.…”
Section: Distinction Of the Mechanical Shaking Systems For Different ...mentioning
confidence: 99%
“…Obviously, almost all of the mechanical shaking systems are employed to harvest fruits for processing industry on account of the fruit damage. While a few researchers investigated that the limb shaking system could also be used for the fresh apple harvesting effectively [23][24][25]29,126] . It indicated that limb shaker with catching device would be a promising pattern to harvest fruits selectively with relative high fruit removal percentage and low fruit injury for fresh fruit market.…”
Section: Distinction Of the Mechanical Shaking Systems For Different ...mentioning
confidence: 99%
“…It is known that shaking is a customary technique for mechanical harvesting of tree fruit. Research and development in the past few decades have successfully produced shaking machines capable of harvesting different fruit tree species (Erdogan et al, 2003;Xing et al, 2020). All these studies have been aimed at evaluating the optimal combination of shaking frequency, amplitude, and duration for harvesting specific types of fruit to achieve maximum fruit-removal efficiency (Castro-Garcıá et al, 2012;He et al, 2019).…”
Section: Introductionmentioning
confidence: 99%